Numerical Analysis of Senggarang Embankment Constructed with Cement-CSP Stabilised Sandy Clay - BAKARI, DALILA; CHAN, CHEE MING (Progress in Engineering Application and Technology, 2021)
Embankment is a structure constructed covering a water body which can be natural water retaining storage like lakes, pond, or artificially constructed water storage structure likes dams. However, there are some failures that can occur in the embankment caused by seepage, piping and foundation instability. The Senggarang embankment is facing severe seepage phenomena which could lead to collapse and critical flooding risk. The seepage problem has severely compromised the stability and safety of the embankment, especially where the inland area is flooded during tide. The objectives of this research are to analyze the seepage characteristics of Senggarang embankment constructed with cement-CSP-stabilised sandy clay and to evaluate the load-bearing capacity of the cement-CSP-stabilised sandy clay embankent with the ‘prescribed displacement approach’. In summary,it was found that discharge of seepage for embankment constructed with cement-CSP stabilised sandy clay was lower than untreated sandy clay embankment. The discharge of seepage using PLAXIS also has been compared with manual calculation using flownet analysis. The average difference was only 22 %. Futhermore, the tide level or water level effect on the seepage and stability of the embankment. The higher the water level, the higher the discharge of seepage. Therefore, mixture of cement-CSP found to be an excellent way to reduce seepage problem in Senggarang embankment.